Choosing the Pond: On-the-Job Experience and Long-Run Career Outcomes - Gong, Jie; Sun, Ang; Wei, Zhichao (Management Science, 2018)
This paper investigates the value of on-the-job experience for workers’ long-run career outcomes. We exploit the effects of team relegation in professional soccer by contrasting players on teams just below and just above the cutoff point of relegation. We find that players on teams relegated to a lower division have more match appearances in the short run, and they play in better leagues and earn higher wages in the long run. This gain is concentrated among individuals who are young or less experienced at the time of relegation. Because other consequences of relegation would tend to work against individuals’ long-run success, the positive net gain is most likely to be the result of greater on-the-job experience. The findings have implications for firms on job assignment and for workers on managing their careers. Data are available at https://doi.org/10.1287/mnsc.2016.2609 . This paper was accepted by Sendil Ethiraj, organizations.